PENGARUH KONSENTRASI LARUTAN KALSIUM HIDROKSIDA (Ca (OH)2) TERHADAP KARAKTERISTIK FISIK DAN KIMIA GELATIN KULIT SAPI - Susan ., Mokoolang; Meity ., Sompie; Indiyah ., Wahyuni (Sam Ratulangi University, 2019)
The aim of the study was to examine the effect of differences in the concentration of lime solution (Ca (OH) 2) on the physical and chemical properties of gelatin in cow skin. This research was conducted in December 2017 until January 2018 at the Laboratory of Animal Product Technology at the Faculty of Animal Husbandry, Sam Ratulangi University of Manado and analysis was carried out at the Food Engineering Laboratory, Faculty of Agricultural Technology, Gadjah Mada University, Yogyakarta. This study used a Completely Randomized Design (CRD) 4 x 4 with the treatment of the concentration of calcium hydroxide (Ca (OH) 2) solution, each treatment was repeated four times (Steel and Torrie, 2001). The results showed that the treatment of the concentration of calcium hydroxide (Ca (OH) 2) gave no significant difference (P> 0.05) on gel strength, viscosity, yield, pH and water content of gelatin in cow skin.*eprm*